Among the young generation, the antecedents and consequences of Intention and Satisfaction affects online banking adoption - Alekam, Jamal Mohammed Esmail; Mohd Mokhtar, Sany Sanuri; Md Salleh, Salniza; Mabkhot, Hashed Ahmad; Shahardin, Nur’izzate Iwana; Rosli, Fatin Nabilah; Asmi, Nor Asniza; Jamian, Nur Hayati; Abdul Amzah, Nur Asyhana Tasneem (2017)
The objective of this study is to finde among the young generation, the antecedents and consequences of Intention and Satisfaction affects online banking adoption through Malaysian Universities students.This study was carried out because lack of studies, only a few studies has examined the influence of security, trust, on the intention to use online banking.and examine the relationship between intention to use online banking and adoption of online banking.In addition satisfaction on the adoption of online banks among young generation.The Partial Least Squares Structural Equation Modelling (PLS-SEM) was employed in the data analysis.The findings revealed a strong significant relationship between the variables.The study concludes with a discussion on the contributions, limitations as well as suggestions for future research.